Teachers Ability to Provide Learning Variations in Thematic Learning in Elementary Schools - Subhan Subhan; Fitria Ningsih (Council: Education Journal of Social Studies, 2024)
In conditions in the field there are still several skills that are not yet visible or fulfilled, many teachers only carry out tasks limited to transferring knowledge without knowing how to package learning to attract students' attention, so that many students are found who lack the motivation to study actively at school, use learning resources which is less than optimal, and the use of models that are less varied or innovative. The aim of the research is to describe conditions in the field regarding the ability of elementary school teachers to carry out thematic learning variations at SDN 70 Tolotongga, Bima City. This research is a qualitative descriptive research. Data collection was carried out in three meetings. The research subjects were class III teachers. The variables in this research are the teacher's skills in providing variations and student responses. The data collection techniques used were observation, interviews and documentation. The results of research at SDN 70 Tolotongga, Bima City, teachers have been able to master the skills in carrying out varied learning very well. Variations in learning are carried out in many ways, both through body movements, sounds, activities that can increase enthusiasm for learning, group formation and the use of learning media. Therefore, teachers' abilities in carrying out variations in thematic learning should continue to be improved in order to minimize the obstacles that arise